RADIOACTIVE WASTE TREATMENT OF OIL AND GAS INDUSTRY - Alifia Darmayanti; Yohannes Sardjono; Sri Yuniarti (Indonesian Journal of Physics and Nuclear Applications, 2018)
The increase of energy needs leads to the increase of oil and gas industry in Indonesia. Along with this, a good understanding about the application of radioactive materials, the treatment of radioactive waste and its disposal is needed. It is important because nowadays the radiation-based technologies are widely used by oil and gas industry, and a good understanding of the mentioned points will enable us to provide better and improved treatment as we strive to achieve clean technology. The uses of radioactive materials in the oil and gas industry are in exploration, producing, refineries, inspection of facilities, laboratories, and industrial security. The treatment of radioactive waste from oil and gas industry are divided into aqueous waste treatment, organic liquid waste treatment, and solid waste treatment.